Organism Models of Autism Spectrum Disorders - Roubertoux, Pierre L.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
As autism is associated with many rare diseases, this extensive bench book examines how no one single model can be used; multiple organism models are needed, each one corresponding to one of the diseases or to one aspect of a disease. Split into five sections, Organism Models of Autism Spectrum Disorders explores selecting the good species for the specific disease, modeling autism spectrum disorders (ASD) at the brain level, studying communication and social interactions, using vertebrates or invertebrate models of ASD as defined by DSM-5R, as well as pursuing models of diseases associated with an increased incidence of ASDs. Written for the respected Neuromethods series, this detailed volume contains the kind of insight and useful, practical advice that ensures more successful results in the lab. Comprehensive and handy, Organism Models of Autism Spectrum Disorders will benefit psychiatrists and geneticists, as well as behavioral researchers who, realizing how important it is to improve their knowledge through more molecular approaches, are looking for the most suitable organisms.
Organism Models: Choosing the Right Model -- The Autistic Spectrum Disorders (ASD) : From the Clinics to the Molecular Analysis -- Selecting the Right Species: Practical Information on Organism Models -- Viewing Animal Models for Tuberous Sclerosis Complex in the Light of Evolution -- In Vivo Imaging in Mice -- Invertebrate Models of Synaptic Transmission in Autism Spectrum Disorders -- Epigenetic Factors in Normal and Pathological Neuronal Development -- Finding Endophenotypes for Autism Spectrum Disorders (ASD): cDNA Microarrays and Brain Transcripts -- Serotonin Disturbance in Mouse Models of Autism Spectrum Disorders -- Communication and Language in Animals -- Social Relationships in Nonhuman Primates: Potential Models of Pervasive Disorders -- Zebrafish Social Behaviour Testing in Developmental Brain Disorders -- Maintaining Mice for Neurobehavioral Examination -- Deficit in Social Relationships and Reduced Field of Interest in Mice -- Modeling Autism Spectrum Disorders Motor Deficits in Mice -- Neuro-Behavioral Testing of Mouse Models of Rett Syndrome -- Mouse Models of Tuberous Sclerosis -- Use of the Zebrafish Model to Understand Behavioral Disorders Associated with Altered Oxytocin System Development: Implications for Autism and Prader-Willi Syndrome -- Epilogue: Perspectives and Caveats.
Keywords: Neurosciences; Neurology .; Animal models in research; Neurosciences; Neurology; Animal Models